DETERMINATION OF SUPPLY CONDITIONS, SCENARIOS AND PAY-OFF FOR INDUSTRIAL MACHINERY SUPPLIER SELECTION POST ECONOMIC AND ENGINEERING CONSIDERATIONS (Nigerian Journal of Technology, 2023)
Supply conditions, the negotiation strategies used for supplier selection after economics and engineering considerations is important for consideration because machinery and equipment procurement is a tripod of which supply conditions is one. This study identified the attributes of supply conditions, different ways (scenarios) of combining the attributes using simple permutation and combination theories and determine the pay-off as well as the opportunity lost to every scenario used by method of Expected Decision Value (EDV). The attributes were identified as: Due – Date of the Supply [A]; Technical Capability of Vendor [B]; After Sales Services [C]; and Vendor’s Experience [D]. Total number of scenarios were 15 of four (4) options. The pay-off with the opportunity lost to each selected option are: Option 1 (25% against 75%) favours supplier; Option 2 (50% against 50%) equally favoured; Option 3 (75% against 25%) favours Purchaser; and Option 4, 100% in favour of purchaser (dominant).